The extent, perceived causes and impacts of land use and land cover change in Tyhume Valley, South Africa - Masiza, Wonga; Hamandawana, Hamisai; Chirima, Johannes George; Khoboko, Pitso; Parkies, Nombuso (Frontiers in Conservation Science, 2023)
There is limited knowledge on how people living in communal areas perceive land use and land cover (LULC) change and the impacts it has on sustainable access to essential ecosystem goods and services. This study used seven wet season Landsat images covering 1989 to 2019 and the Extreme Gradient Boosting algorithm to map LULC in Tyhume Valley, South Africa. Analyses of trends in LULC and long-term changes in rainfall over the same period were based on the Mann Kendall (MK) statistical technique. Perceptions on the causes and impacts of the observed trends were solicited from 102 respondents and summarized through frequency analysis. Major trends that emerged from image-based analysis include the expansion of Vachellia karroo by 25% (τ = 0.98; p = 0.004), decrease in pastureland by 18% (τ = -0.90, p = 0.007), decrease in cropland by 9.6% (τ = -0.90, p = 0.007), decrease in surface water by 1.1% (-0.90, p = 0.007), and increase in built-up area by 2.5% (τ = 1.00, p = 0.003). Perceived causes of these trends include the eradication of land access control systems, poor management of surface water, lack of farmer support programs, and 14 years of negative rainfall anomalies. The impacts of these changes include long-distance trekking of animals to pastures and watering points, increased livestock malnutrition and mortality, decline of medicinal and culturally significant trees, increased purchasing of stock feed, increased unemployment, and 2 This is a provisional file, not the final typeset article consumption of unhealthy food. The study concludes by highlighting the need to accommodate local perceptions in the formulation of policies and practices for sustainable use of ecosystem services.